Penerapan strategi Problem Based Learning (PBL) Untuk Meningkatkan Aktivitas Peserta Didik Dalam Pembelajaran Akidah Akhlak Kelas VIII di Mts Khozinatul Ulum Blora - Fera Dwi Cahya; Muhammad Nabil; Muhammad Zainal Abidin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to describe the implementation of Problem Based Learning (PBL) strategy in improving student learning activities in Akidah Akhlak subject for class VIII at MTs Khozinatul Ulum Blora. A qualitative descriptive approach was employed. Data were collected through participatory observation, in-depth interviews, and documentation. The results showed that the PBL implementation proceeded through five systematic syntaxes with the teacher as facilitator. This strategy significantly improved student learning activities across visual, oral, writing, mental, and emotional dimensions. Supporting factors included the principal's support, teacher creativity, and the religious school culture, while inhibiting factors included limited time allocation and restricted access to digital information.